The Differentiation of CD4+ T-Helper Cell Subsets in the Context of Helminth Parasite Infection - Bouchery, Tiffany; Kyle, Ryan; Ronchese, Franca; Le Gros, Graham (Frontiers in Immunology, 2014)
Helminths are credited with being the major selective force driving the evolution of the so-called “type 2” immune responses in vertebrate animals, with their size and infection strategies presenting unique challenges to the immune system. Originally, type 2 immune responses were defined by the presence and activities of the CD4+ T-helper 2 subset producing the canonical cytokines IL-4, IL-5, and IL-13. This picture is now being challenged by the discovery of a more complex pattern of CD4+ T-helper cell subsets that appear during infection, including Tregs, Th17, Tfh, and more recently, Th22, Th9, and ThGM. In addition, a clearer view of the mechanisms by which helminths and their products selectively prime the CD4+ T-cell subsets is emerging. In this review, we have focused on recent data concerning the selective priming, differentiation, and functional role of CD4+ T-helper cell subsets in the context of helminth infection. We argue for a re-evaluation of the original Th2 paradigm and discuss how the observed plasticity of the T-helper subsets may enable the parasitized host to achieve an appropriate compromise between elimination, tissue repair, containment, and pathology.